(untitled) (Journal of Medical & Health Sciences Review, 2025)
Objective: This study aimed to assess the association between spiritual well-being and the quality of life among end-stage renal disease (ESRD) patients undergoing hemodialysis (HD). Methodology: An analytical cross-sectional study was conducted at two public healthcare settings, the Institute of Kidney Disease and Lady Reading Hospital in Peshawar, Khyber Pakhtunkhwa (KPK). The sample, comprising 377 ESRD patients on a minimum of 6 months of hemodialysis, was selected using consecutive sampling. Data on spiritual well-being and quality of life were collected using the Urdu versions of the Spiritual Well-Being (SWB) scale and Quality of Life (QOL) scale, both with alpha-Cronbach’s reliability coefficients of 0.82 and 0.74, respectively. Social and demographic data were also collected. Result: The study revealed a strong positive correlation (0.721, p<0.01) between SWB and QOL. Statistical significance was observed between these two variables (Chi-square = 81.511, p<0.001). Most participants exhibited a moderate to high level of total spiritual well-being (SWB) and a low to moderate level of quality of life (QOL). Additionally, the study explored the relationship between demographic variables and QOL and Spiritual Well-being. Conclusion: Spiritual well-being (SWB) was found to have a positive impact on the quality of life (QOL) of HD patients. Consequently, health systems, within the holistic framework of individual care, are encouraged to incorporate spiritual evaluation and care for HD patients. The findings emphasize the need for individualized treatment and care plans, recognizing the influence of socio-demographic factors on patients with the same disease.